2014
DOI: 10.1002/2014gl062400
|View full text |Cite
|
Sign up to set email alerts
|

Increases in plasma sheet temperature with solar wind driving during substorm growth phases

Abstract: During substorm growth phases, magnetic reconnection at the magnetopause extracts ∼1015 J from the solar wind which is then stored in the magnetotail lobes. Plasma sheet pressure increases to balance magnetic flux density increases in the lobes. Here we examine plasma sheet pressure, density, and temperature during substorm growth phases using 9 years of Cluster data (>316,000 data points). We show that plasma sheet pressure and temperature are higher during growth phases with higher solar wind driving, wherea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 55 publications
1
34
0
Order By: Relevance
“…They have revealed that although ~ 59.0% of our events correspond to a P eqend increase, there are still events with P eqend almost unchanged (~ 28.0%) or even decreasing (~ 13.0%) as compared to P eq0 . We believe that these results may provide an explanation for the previous conflicting results concerning plasma sheet pressure variations, that is, some showing plasma sheet pressure increase during the substorm growth phase (e.g., Forsyth et al, ; Kistler et al, ; Nagai et al, ; Wang et al, ), while others found little or no change (e.g., Kistler et al, ; Snekvik et al, ). We have found that the P eq increase percentage at the end of growth phase is the highest in the premidnight MLT bin (22:00 to 00:00).…”
Section: Conclusion and Discussionmentioning
confidence: 68%
See 3 more Smart Citations
“…They have revealed that although ~ 59.0% of our events correspond to a P eqend increase, there are still events with P eqend almost unchanged (~ 28.0%) or even decreasing (~ 13.0%) as compared to P eq0 . We believe that these results may provide an explanation for the previous conflicting results concerning plasma sheet pressure variations, that is, some showing plasma sheet pressure increase during the substorm growth phase (e.g., Forsyth et al, ; Kistler et al, ; Nagai et al, ; Wang et al, ), while others found little or no change (e.g., Kistler et al, ; Snekvik et al, ). We have found that the P eq increase percentage at the end of growth phase is the highest in the premidnight MLT bin (22:00 to 00:00).…”
Section: Conclusion and Discussionmentioning
confidence: 68%
“…The transmission of enhanced electric fields associated with dayside magnetopause reconnection across the open field lines of the magnetotail has been extensively studied (e.g., McPherron et al, ; Russell & McPherron, ). The enhanced electric field due to solar wind convection transports reconnected (i.e., “open”) magnetic flux from the dayside into lobes and has been believed to be responsible for an increase in total pressure in the plasma sheet (e.g., Forsyth et al, ; Kistler et al, ; Wang et al, ; Yue et al, ). However, it has also been suggested that this enhanced electric field will be reflected in the closed field line region of the near tail through compression and rarefaction waves (Coroniti & Kennel, ; Kan, ).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…During the growth phase, low-latitude dayside reconnection with the IMF (interplanetary magnetic field) dominates over the nightside reconnection rate, resulting in an accumulation of open field lines in a highly stretched magnetotail (Kokubun & McPherron, 1981;McPherron, 1970McPherron, , 1972Milan et al, 2007). The dipolarization of the magnetic field and the destabilization of the near-Earth tail act to energize particles and drive intense electric currents (e.g., Forsyth et al, 2014;McPherron et al, 1973). The dipolarization of the magnetic field and the destabilization of the near-Earth tail act to energize particles and drive intense electric currents (e.g., Forsyth et al, 2014;McPherron et al, 1973).…”
Section: Introductionmentioning
confidence: 99%